Integrating systemic inflammation and liver biomarkers: prognostic implications of the ferritin index in heart failure - Ching-Hui Huang; Chew-Teng Kor; Chia-Chu Chang (Annals of Medicine)
Background Heart failure (HF) is increasingly recognized as a multisystem syndrome involving systemic inflammation and metabolic dysfunction in addition to cardiac and hepatic impairment. Traditional liver fibrosis scores, such as the fibrosis-4 (FIB-4) index, focus solely on hepatic injury and may underestimate the broader systemic burden. The ferritin index, which adjusts serum ferritin for age and sex, may better reflect inflammatory and metabolic dysregulation, including features of metabolic hyperferritinaemia. This study aimed to evaluate the prognostic value of the ferritin index versus the FIB-4 score in predicting major adverse cardiovascular events (MACE) in patients with HF.Materials and methods This retrospective cohort study included 751 HF patients from the Changhua Christian Hospital Clinical Research Database, spanning all ejection fraction categories. Cox regression models were used to assess associations between MACE and tertiles of ferritin index and FIB-4 score, with adjustments for baseline characteristics.Results Patients in the highest ferritin index tertile had significantly increased MACE risk (adjusted hazard ratio 1.92; p = 0.003). This association remained robust in the sensitivity and subgroup analyses. The FIB-4 score was not significantly associated with MACE. Subgroup analysis showed stronger associations in patients aged ≥70 years, with higher BMI (≥24 kg/m2), reduced EF, low FIB-4 (<1.45), and abnormal hemoglobin or iron levels.Conclusion The ferritin index outperforms the FIB-4 score in predicting MACE in HF patients. By integrating systemic inflammatory and metabolic signals, it improves risk stratification, especially in those with features of metabolic hyperferritinaemia.